Adherence to National Consensus Guidelines and Association with Clinical Outcomes in Patients with Candidemia. (June 2021) - Junco, Shauna Jacobson; Chehab, Sarah; Giancarelli, Amanda; Bowman, Mary Catherine; Turner, R Brigg
Background: National consensus guidelines outline recommendations for best practices in treating patients with candidemia. This study evaluated the impact of receiving care adherent to the best practice recommendations on clinical outcomes in patients with candidemia. Methods: This retrospective, multicenter study included patients with candidemia from 2010 to 2015 at 9 hospitals. The primary outcome was the composite of 30-day in-hospital mortality and 90-day candidemia recurrence. Outcomes were compared between those receiving and not receiving care adherent to the guideline recommendations. Inverse probability weights with regression adjustment were utilized to determine the average treatment effect of adherent care on the composite outcome Results: 295 patients were included with 14.2% meeting criteria for the composite outcome (11.9% mortality and 2.4% recurrence). The average treatment effect of adherent care was not significant ( P  = .75). However, receiving appropriate initial antifungal treatment and central venous catheter removal were both associated with the composite (average treatment effect of −17.5%, P  = .011 and −8.8%, P  = .013, respectively). In patients with a source of infection other than the central line, central venous catheter removal was not associated with the composite ( P  = .95). The most common reason for failure to receive appropriate initial antifungal treatment was omission of the loading dose. Conclusions: Central venous catheter removal and appropriate initial antifungal treatment were associated with a lower incidence of the composite of mortality and recurrence. Additional studies are needed to determine the optimal duration of therapy following candidemia clearance.